2022
DOI: 10.1016/j.ahjo.2022.100084
|View full text |Cite
|
Sign up to set email alerts
|

Arrhythmia patterns during and after hospitalization for COVID-19 infection detected via patch-based mobile cardiac telemetry

Abstract: Background Coronavirus infection is the cause of the current world-wide pandemic. Cardiovascular complications occur in 20–30% of patients with COVID-19 infection including myocardial injury and arrhythmias. Current understanding of specific arrhythmia type and frequency is limited. Objective We aimed to analyze arrhythmia type and frequency in patients with COVID infection, identifying arrhythmia patterns over time during hospitalization and post discharge utilizing a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 24 publications
0
2
0
1
Order By: Relevance
“…9 Current studies confirm the presence of these findings using telemetry devices, identifying at least one episode of arrhythmia in 73% of cases analyzed, with a possible increase during the evolution of the disease. 41 Other findings, such as changes in the ST segment, have also been reported during COVID-19, either mimicking an acute coronary syndrome or as a manifestation of other cardiovascular complications, including myocarditis or pericarditis. 42 Another important aspect is use of pharmacological therapies with effects on the cardiovascular system, such as macrolides and hydroxychloroquine, which have been reported in our study in 46.5% and 11.5% of cases, respectively, compared with the results of other studies that reported frequency of use of up to 80%.…”
Section: Discussionmentioning
confidence: 92%
“…9 Current studies confirm the presence of these findings using telemetry devices, identifying at least one episode of arrhythmia in 73% of cases analyzed, with a possible increase during the evolution of the disease. 41 Other findings, such as changes in the ST segment, have also been reported during COVID-19, either mimicking an acute coronary syndrome or as a manifestation of other cardiovascular complications, including myocarditis or pericarditis. 42 Another important aspect is use of pharmacological therapies with effects on the cardiovascular system, such as macrolides and hydroxychloroquine, which have been reported in our study in 46.5% and 11.5% of cases, respectively, compared with the results of other studies that reported frequency of use of up to 80%.…”
Section: Discussionmentioning
confidence: 92%
“…As COVID-19 is a systemic hyperinflammatory disease significantly impairing respiratory function, and the latter factors have long been known as being pro-arrhythmic in many other clinical entities, these assumptions are fully justified, while the mentioned mechanisms most likely contribute to the development of COVID-19-driven arrhythmias. However, mechanistic studies on the arrhythmia pathogenesis in the specific context of SARS-CoV-2 infection are lacking, and an abnormal heart rhythm has been found to be frequent in recovered patients [ 7 ], as well as in patients with mild symptomatology [ 3 ], who are not hypoxemic and do not have a hyperinflammatory response.…”
Section: Discussionmentioning
confidence: 99%
“…As arritmias cardíacas relacionadas ao COVID-19 apresentam-se como segunda maior complicação da infecção, perdendo apenas para Hipertensão Arterial (HONARDOOST, et al, 2021), sendo as atriais as mais comuns e indutoras de quadros mais graves que as arritmias ventriculares (REYNBAKH, et al, 2022). Em estudo conduzido com 241 pacientes internados por COVID-19, as arritmias pós infecção se desenvolveram em 21% deles (PIMENTEL, et al, 2021).…”
Section: Fibrilação E Covid-19unclassified